Incidence, Risk Factors, and Outcomes of Hyperbilirubinemia in Adult Cardiac Patients Supported by Veno‐Arterial ECMO. Issue 2 (6th September 2017) - Lyu, Lin; Yao, Jingxin; Gao, Guodong; Long, Cun; Hei, Feilong; Ji, Bingyang; Liu, Jinping; Yu, Kun; Hu, Qiang; Hu, Jinxiao
Abstract: The aims of this study were to evaluate the incidence, risk factors, and outcomes of hyperbilirubinemia in cardiac patients with veno‐arterial (VA) ECMO. Data on 89 adult patients with cardiac diseases who received VA ECMO implantation in our hospital were retrospectively reviewed. All patients were divided into the following three groups: 24 in normal group (N, total bilirubin [TBIL] ≤3 mg/dL), 30 in high bilirubin group (HB, 6 mg/dL ≥ TBIL > 3 mg/dL), and 35 in severe high bilirubin group (SHB, TBIL > 6 mg/dL). lg(variables + 1) was performed for nonnormally distributed variables. The incidence of hyperbilirubinemia (>3 mg/dL) was 73%. In a multiple linear regression analysis, lg(peak TBIL + 1) was significantly associated with lg(peak AST + 1) ( b ‐coefficient 0.188, P = 0.001), lg(peak pFHb + 1) ( b ‐coefficient 0.201, P = 0.003), and basic TBIL ( b ‐coefficient 0.006, P = 0.009). Repeated measurement analysis of variance revealed that the main effect for three groups in pFHb and lg(AST + 1) was significant at first 3 days during ECMO. The patients in SHB had low platelets during ECMO and low in‐hospital survival rate. Hyperbilirubinemia remains common in patients with VA ECMO and is associated with low platelets and high in‐hospital mortality. Hemolysis and liver dysfunction during ECMO and basic high bilirubin levels are risk factors of hyperbilirubinemia.